THE EFFECTS OF TRADE LIBERALIZATION BETWEEN INDONESIA AND JAPAN: A CASE TO INDONESIAN ECONOMY - Nugroho, Ario Seno (Politeknik Keuangan Negara STAN)
This paper examines the effects of free trade between Indonesia and Japan on agriculture and manufacturing sector, consumer welfare, and the whole economy in Indonesia using a computable general equilibrium model based on 2008 Indonesia Input-Output Table. The general theory related to the effects of free trade says domestic consumers will benefit while disadvantages domestic producers will suffer from the free trade policy. In contrast, this study found that both the domestic consumers and the domestic industries (people who work in industries) benefit from trade liberalization scenario. The consumer welfare and economics utility would also increase. Also, the model estimates the reduction in government revenue, which is caused by decreasing tariff, is lower than the addition in government revenue from non-tariff income. Finally, manufacturing sector seems has the highest benefit from trade liberalization while in the agriculture sector is estimated minor outcomeÂ